Dietary supplementation of nucleotides and oligosaccharides in kittens reduces the expression of circulating miR-1-3p, miR-133a-3p, miR-206-3p and miR-383-5p - Albanese, Fabio; Harrison, Matthew; Farquhar, Michelle J.; Holcombe, Lucy J.; Atwal, Jujhar; Watson, Phil; Piccinini, Anna M. (Frontiers in Veterinary Science, 2025)
The immune system of kittens is less efficient at fighting pathogens compared to adult cats with kittens being more susceptible to infections. Increasing evidence shows that dietary interventions can enhance immunity in mammals and modulate the expression of microRNAs (miRNAs) with key immune functions, however research in kittens is limited. Diets that can enhance the ability of a kitten's developing immune system to successfully fight infections, and where effects can be monitored by veterinarians, are highly sought-after. Here, we utilised small RNA sequencing (RNA-Seq) to investigate the effects of an experimental (test) diet containing nucleotides and oligosaccharides on the global expression of circulating miRNAs in 23-week-old kittens (n = 9). Furthermore, we determined whether these effects were sustained up to 10 weeks post-supplementation. Kittens fed with the test diet were found to have a lower expression of a specific subset of circulating miRNAs, namely miR-1-3p, miR-133a-3p, miR-206-3p and miR-383-5p, compared to animals fed with a control diet. Notably, this effect persisted 10 weeks post-supplementation. Bioinformatics analysis indicated that these miRNAs target immune-related genes and pathways. As such, they may hold potential as biomarkers to monitor immune performance of kittens and inform the prescription of veterinary diets.